Clinical Features, Severity, and Incidence of RSV Illness During 12 Consecutive Seasons in a Community Cohort of Adults ≥60 Years Old. (27th November 2018) - Belongia, Edward A; King, Jennifer P; Kieke, Burney A; Pluta, Joanna; Al-Hilli, Ali; Meece, Jennifer K; Shinde, Vivek
Abstract: Background: The epidemiology and burden of respiratory syncytial virus (RSV) illness are not well defined in older adults. Methods: Adults ≥60 years old seeking outpatient care for acute respiratory illness were recruited from 2004–2005 through 2015–2016 during the winter seasons. RSV was identified from respiratory swabs by multiplex polymerase chain reaction. Clinical characteristics and outcomes were ascertained by interview and medical record abstraction. The incidence of medically attended RSV was estimated for each seasonal cohort. Results: RSV was identified in 243 (11%) of 2257 enrollments (241 of 1832 individuals), including 121 RSV type A and 122 RSV type B. The RSV clinical outcome was serious in 47 (19%), moderate in 155 (64%), and mild in 41 (17%). Serious outcomes included hospital admission (n = 29), emergency department visit (n = 13), and pneumonia (n = 23) and were associated with lower respiratory tract symptoms during the enrollment visit. Moderate outcomes included receipt of a new antibiotic prescription (n = 144; 59%), bronchodilator/nebulizer (n = 45; 19%), or systemic corticosteroids (n = 28; 12%). The relative risk of a serious outcome was significantly increased in persons aged ≥75 years (vs 60–64 years) and in those with chronic obstructive pulmonary disease or congestive heart failure. The average seasonal incidence was 139 cases/10 000, and it was significantly higher in persons with cardiopulmonary disease compared with others (rate ratio, 1.89; 95% confidence interval, 1.44–2.48). Conclusions: RSV causes substantial outpatient illness with lower respiratory tract involvement. Serious outcomes are common in older patients and those with cardiopulmonary disease.